2022
DOI: 10.1115/1.4055388
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature and Velocity on Microparticle Erosion/Deposition into Environmental-Barrier-Coated Ceramic Matrix Composite for Aeroengines

Abstract: Ceramic matrix composites (CMCs), especially SiC/SiC, have garnered significant attention owing to their remarkable mechanical properties at higher temperatures. For protection of the substrate from oxidation, the SiC/SiC CMCs inherently require environmental barrier coating (EBC). Because aeroengines must function under a wide range of conditions and environments, the coated CMC must be sufficiently resistant to various damage modes. Among these, the effect of microparticles is one of the limiting factors for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…77 A recent study showed that the melting and crystallization properties of synthetic CMAS compositions is highly dependent on the CaO:SiO 2 ratio where the initial onset of melting occurred as low as ∼1050 • C while full melting temperatures could occur as high as 1,500 • C. 78 This suggests that SPE can still occur at operating temper-atures as high as 1500 • C. As a result, the gas temperature, particle composition, and particle velocity/kinetic energy will determine the mode of damage: only erosion, erosion plus deposition, only deposition, or no erosion nor deposition. 79 Current techniques for evaluating CMAS corrosion of EBCs have been focused on static loading where the CMAS is applied to the surface at ambient temperature and then melted/reacted in a furnace. 80 In application, CMAS deposition, and correspondingly, SPE and the synergistic effects between the two modes (erosion-corrosion) are dynamic in nature.…”
Section: Erosion-corrosionmentioning
confidence: 99%
See 3 more Smart Citations
“…77 A recent study showed that the melting and crystallization properties of synthetic CMAS compositions is highly dependent on the CaO:SiO 2 ratio where the initial onset of melting occurred as low as ∼1050 • C while full melting temperatures could occur as high as 1,500 • C. 78 This suggests that SPE can still occur at operating temper-atures as high as 1500 • C. As a result, the gas temperature, particle composition, and particle velocity/kinetic energy will determine the mode of damage: only erosion, erosion plus deposition, only deposition, or no erosion nor deposition. 79 Current techniques for evaluating CMAS corrosion of EBCs have been focused on static loading where the CMAS is applied to the surface at ambient temperature and then melted/reacted in a furnace. 80 In application, CMAS deposition, and correspondingly, SPE and the synergistic effects between the two modes (erosion-corrosion) are dynamic in nature.…”
Section: Erosion-corrosionmentioning
confidence: 99%
“…Erosion-corrosion studies have been performed for TBCs, but this area remains largely unexplored for EBCs. It is worth noting that Okita et al 79 performed an initial investigation on the effect of temperature and velocity for microparticle erosion/deposition on an EBC/CMC using crushed quartz particles. The results showed general agreement with a critical viscosity model where deposition dominated below the critical viscosity of quartz (silica) and erosion dominated above the critical viscosity.…”
Section: Erosion-corrosionmentioning
confidence: 99%
See 2 more Smart Citations